2017
DOI: 10.3748/wjg.v23.i22.4016
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofCXCR3/HO-1genes modified bone marrow mesenchymal stem cells on small bowel transplant rejection

Abstract: AIMTo investigate whether bone marrow mesenchymal stem cells (BMMSCs) modified with the HO-1 and CXCR3 genes can augment the inhibitory effect of BMMSCs on small bowel transplant rejection.METHODSLewis rat BMMSCs were cultured in vitro. Third-passage BMMSCs were transduced with the CXCR3/HO-1 genes or the HO-1 gene alone. The rats were divided into six groups and rats in the experimental group were pretreated with BMMSCs 7 d prior to small bowel transplant. Six time points (instant, 1 d, 3 d, 7 d, 10 d, and 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 78 publications
2
22
0
Order By: Relevance
“…However, we did not perform any pathway blocking experiments and only demonstrated the role of monocytes. Our team previously studied the role of stem cells in the functioning of the corresponding immune cells of the innate and adaptive immunity in transplant recipients [30,45]. In future, we aim to study the role of other immune cells by blocking major signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not perform any pathway blocking experiments and only demonstrated the role of monocytes. Our team previously studied the role of stem cells in the functioning of the corresponding immune cells of the innate and adaptive immunity in transplant recipients [30,45]. In future, we aim to study the role of other immune cells by blocking major signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation and identification of BMMSCs was performed as previously described [30,31]. BMMSCs transfected with Ad/HO-1 showed no morphological changes, with a typical spindle-shaped appearance (Fig.…”
Section: Characterization Of Ho-1/bmmscs and Increased Expression Of mentioning
confidence: 99%
“…CXCR3 receptors bind to their specific ligands [monokine induced by interferon (IFN)-γ, IFN-γ-inducible protein 10 and IFN-γ-inducible T-cell α chemoattractant], and recruit CXCR3-expressing cells to the site of injury (16,17). It has been shown that, following transfection with the CXCR3 gene, BMMSCs are chemotactically directed to migrate to a transplanted intestine; this was shown by the increased homing of BMMSCs and inhibited chemotaxis of T cells to transplanted intestine, resulting in protective effects on the transplanted small bowel (18). In our preliminary study, HO-1 and CXCR3 genes were transfected into BMMSCs in vitro , and subsequently transfused into a rat model of rejection to small bowel transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…In our preliminary study, HO-1 and CXCR3 genes were transfected into BMMSCs in vitro , and subsequently transfused into a rat model of rejection to small bowel transplantation. The results showed that the HO-1 and CXCR3 gene-modified BMMSCs were significantly increased in the damaged sites, and the function of the damaged intestine quickly recovered (18). However, the mechanism by which the recovery of intestinal function was achieved remains to be elucidated and requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation